If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3.6h = -14.4 Solving 3.6h = -14.4 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Divide each side by '3.6'. h = -4 Simplifying h = -4
| 22x+70=17x-9 | | X^(3/2)-3x^(1/2)=0 | | 6=0.5*b*4 | | 5x-2/5=49/10 | | 10x+(-50)+68=-32 | | 3x-1=.2 | | w-3=-5 | | 2-1-3y/4=y | | 5x^2-73x+30=0 | | 5x-3=6x-9 | | -9x+37=-5x-11 | | 0=5x^2+6x+5 | | y=-7x^2 | | 7(2)+4y=2 | | 2X-8=13-3x | | 24+3=3x+3(7-1) | | 3x+7+2=33 | | 2X-8=3X-13 | | 180=90+5x+x | | 5(x-1.5)=22.5 | | d/dx(f(3x2))=5x4 | | 3(n-7)=30 | | 2(r^2+16r+16)=0 | | d/dx(f(3x22))=5x4 | | 124=-2-6(-4x-1) | | 7(r-9)=147 | | x=4042.25-3766 | | u^2+6u-72=0 | | 180=(3x-18)+2x+x | | x-4+6=x | | a=r(c/×) | | -2(2x+5)-4= |